Pelatihan Dan Sosialisasi Aplikasi Rencana Detail Tata Ruang (RDTR) Real-Time - Gunawan Pria Utama; Bima Cahya Putra; Dian Anubhakti (Jurnal Pengabdian kepada Masyarakat TEKNO (JAM-TEKNO), 2023)
Carry out spatial planning and achieve justice for all parties involved in the spatial planning process. The implementation of spatial planning is carried out based on spatial planning which functions as a reference for spatial utilization activities, including investment activities and issuance of business permits. The product of spatial planning is in the form of spatial plans which are divided into national spatial plans (RTRWN), national strategic area spatial plans (RTR KSN), island, regency/city regional spatial layout plans (RTRW) and detailed spatial planning plans (RDTR ). The purpose of this work is the realization of a Real-Time RDTR application that has minimal errors and the use and utilization of the Real-Time RDTR Application by spatial planning forums and stakeholders related to spatial planning, especially state apparatus in various regions. related theory, practice of using the application, question and answer and also discussion with the participants. .Training This application will help RDTRs that have regional regulations but are not yet integrated with OSS, thus helping spatial planning forums to make confirmation/approval decisions on the conformity of spatial use activities (KKPR) which are still manual, assisting the RDTR revision process and socializing this real time RDTR application so that Spatial planning forums or regional governments are not afraid to use them.